2021
DOI: 10.1002/mar.21535
|View full text |Cite
|
Sign up to set email alerts
|

Grateful compliance: Gratitude effects on willingness to comply with responsible drinking messages

Abstract: Individuals have a tendency to push back against threats and impositions from others that impinge on their perceived freedom. This issue is prevalent among issues with directive messages especially those in social marketing, such as responsible drinking messages. The current research investigates the potential role of gratitude in increasing individuals' willingness to comply with a responsible drinking message. Across four experimental studies, the present research shows that gratitude, as compared with pride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…), fitting with our SEB focus. We in turn posit SEB conformity to facilitate cooperation, SEB compliance to be conducive to coopetition, and SEB reactance to foster competition in the influencor/influencee relationship (Deutsch & Gerard, 1955;Septianto & Garg, 2021;Wolf et al, 2021), revealing key insight. This conceptual paper makes the following contributions to the marketing-based stakeholder engagement (behavior) literature.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…), fitting with our SEB focus. We in turn posit SEB conformity to facilitate cooperation, SEB compliance to be conducive to coopetition, and SEB reactance to foster competition in the influencor/influencee relationship (Deutsch & Gerard, 1955;Septianto & Garg, 2021;Wolf et al, 2021), revealing key insight. This conceptual paper makes the following contributions to the marketing-based stakeholder engagement (behavior) literature.…”
Section: Introductionmentioning
confidence: 95%
“…Social influence can manifest in different ways, including through conformity (e.g., Deutsch & Gerard, 1955;Gonçalves et al, 2020), compliance (e.g., Cialdini & Goldstein, 2004;Septianto & Garg, 2021), and reactance (e.g., Clee & Wicklund, 1980;G. Lee & Lee, 2009), among others, as discussed further below.…”
Section: Social Influencementioning
confidence: 99%
See 1 more Smart Citation
“…We intentionally tested the context of incidental emotions because such examinations provide empirical evidence with high internal validity (Han et al, 2007). Indeed, prior research has demonstrated that the effects of incidental and integral emotions are consistent (Cavanaugh et al, 2015; Duhachek et al, 2012; Lerner & Keltner, 2001; Septianto & Garg, 2021). As such, by investigating incidental and integral emotions, our findings offered strong empirical evidence to our predictions.…”
Section: Theoretical Developmentmentioning
confidence: 94%
“…While marketers have widely employed emotional appeals in advertising (Dooley, 2009; Pham et al, 2013; Poels & Dewitte, 2019), the examination of emotional appeals in advertising has mostly focused on positive emotions (Cavanaugh et al, 2015; Poels & Dewitte, 2019; Septianto & Garg, 2021). However, consumers often experience mixed emotions (i.e., negative and positive emotions at the same time) across important events (e.g., wedding day, graduation day; Deng et al, 2016) and common situations (e.g., watching horror movies, listening to music; Heavey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%